Evaluasi Tingkat Kesuksesan Pembelajaran Ips Berbasis Taksonomi Bloom Dua Dimensi Kurikulum KTSP 2006 di Sekolah Dasar Negeri 3 Borok Toyang Tahun Pelajaran 2020-2021 - Kurniawan, Muh. Sutrisna (khatulistiwa, 2022)
This study aims to develop and produce a viable evaluation tool for elementary students. This development research will be tested by using two dimensional Bloom taxonomy to produce test grains. The method used in this research is the R & D method (Research and Development) or the research and development method. The evaluation tool developed in this research is about test description, answer key, and scoring guidance. The stages in this study begin with literature study, grating making, test item writing, expert test (content validity), revision phase 1, a limited test consisting of item validity, reliability test, level of difficulty, and differentiation. Then proceed to the revision phase 2, a wider trial of three SDs with one SDN 3 complex, up to test selection and assembly, until a valid and reliable test item is obtained. Evaluation of learning result of IPS subjects by using Bloom's Taxonomy Two Dimensions of the total validation value given by validator to evaluation tool of 3.29, evaluation tool developed in the very valid category and the validity coefficient of item from problem 1 to 30 has high validity criterion. The reliability coefficients of the test questions were developed at 1.019524 with the category of reliability being very high.